Influencia del maltrato intrafamiliar en los comportamientos sociales de los estudiantes de séptimo año de educación básica de la escuela ¨Fe y Alegría¨ de la ciudad de Riobamba, provincia de Chimborazo, durante el primer quimestre, período septiembre 2015 – febrero 2016 - Gómez Abarca, Evelyn Andrea (2016)
This research has the general objective to determine the influence of domestic abuse in social behavior of students in Seventh Year Basic Education School "FE Y ALEGRÍA" of Riobamba city, Chimborazo province, during the first quimestre, period September 2015 - February 2016. It is field research because the data were collected at the scene, with type of cross-sectional study that information was collected in a given time; the overall objective of it is to determine the influence of domestic abuse in social behavior of the students; the specific objectives are: to investigate the level of domestic abuse in students analyze social behaviors of the students and finally to investigate the influence of domestic abuse in social behavior. To carry out the proposed research, it is determined that is important to work for the variable social behaviors with test called the BAS 3 (Battery Self-Assessment of socialization) to the stage of domestic abuse we performed a survey of parents was held, this was tabulated, analyzed and interpreted. Resulting in a high withdrawal by 71% of students because of their psychologist affectivity in their environment, and 66% of parents who believe that domestic violence affects how humans act. This research is a contribution for students, teachers and parents and society in general.